Methodological Methods Of Teaching Children For Movement Activities In The Process Of Physical Education Classes - L.A.Azimov; M.A.Ruzimboev (Research Parks Publishers, 2021)
The article discusses the methodological methods of teaching children physical activity in the process of physical education and the methodological methods used in teaching children physical activity